Presocratics. - Warren, James (Ancient philosophies., 2014)
The earliest phase of philosophy in Europe saw the beginnings of cosmology and rational theology, metaphysics, epistemology, and ethical and political theory. It saw the development of a wide range of radical and challenging ideas: from Thales' claim that magnets have souls and Parmenides' account that there is only one unchanging existent to the development of an atomist theory of the physical world. This general account of the Presocratics introduces the major Greek philosophical thinkers from the sixth to the middle of the fifth century BC. It explores how we might go about reconstructing t.